Disinformasi dan Kesehatan Masyarakat: Pelajaran dari Pandemi COVID-19 - Gunawan Widjaja; Dyah Ersita Yustanti (Bulletin of Community Engagement, 2025)
The COVID-19 pandemic has not only brought challenges in the health sector, but also given rise to the phenomenon of disinformation that has had a significant impact on public health. This study aims to identify patterns of dissemination and the impact of COVID-19-related disinformation, as well as to formulate effective mitigation strategies through a literature review of various scientific literature and research reports. The results of the analysis indicate that misinformation spreads massively through social media, instant messaging apps, and mass media, with patterns that exploit public emotional sentiment and uncertainty. The impact of misinformation includes a decline in compliance with health protocols, scepticism about vaccination, and a decline in public trust in health institutions and the government. The recommended mitigation strategies include improving digital and health literacy, strengthening regulations, promoting cross-sector collaboration, and optimising data-driven public communication and transparency. These findings underscore the importance of synergies among various parties in building public information resilience to face similar crises in the future